SPE International Symposium and Exhibition on Formation Damage Control 2014
DOI: 10.2118/168215-ms
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Wellbore Cleanup Challenges in Deepwater Wells in West Africa

Abstract: Mesophase technology for wellbore cleanup and remediation in the drilling industry has been used in various oil fields to increase well productivity and injectivity. The majority of these applications include oil-based mud filter cake removal, nearwellbore remediation, and wellbore displacement. The openhole wells completed with standalone screens in deepwater tertiary formations offshore West Africa have benefited from previous knowledge and experiences accumulated by the operator and the servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The injection of hot oil or hot water is used as the thermal treatment (Zhang et al 2020;Creek 2012;Ding et al 2017). The chemical treatment primarily refers to the injection of acid and other chemical solvents (Davudov et al 2018;Pietrangeli et al 2014). Therefore, in the early stage the injection of hot water and inorganic acid is used to remove the wellbore compound blockages for most blockage wells of Yuanba gas field.…”
Section: Introductionmentioning
confidence: 99%
“…The injection of hot oil or hot water is used as the thermal treatment (Zhang et al 2020;Creek 2012;Ding et al 2017). The chemical treatment primarily refers to the injection of acid and other chemical solvents (Davudov et al 2018;Pietrangeli et al 2014). Therefore, in the early stage the injection of hot water and inorganic acid is used to remove the wellbore compound blockages for most blockage wells of Yuanba gas field.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that microemulsion fluids were able to effectively remove synthetic and oil-based filter cake and the near-wellbore damage. For successful operations, the microstructure of microemulsion should be characterized to customize the microemulsions for a certain application [29,30].…”
Section: Introductionmentioning
confidence: 99%